2005
DOI: 10.1080/17453670510045570
|View full text |Cite
|
Sign up to set email alerts
|

Polymethylmethacrylate causes prolonged pulmo-nary hypertension during fat embolism: A study in sheep

Abstract: Background Fat embolism (FE), the release of bone marrow contents into the circulation and the subsequent cardiovascular changes, is still a potentially fatal complication during orthopedic surgery. Different causative factors have been suggested, but the exact pathomechanism of FE still remains unclear. We investigated the role of polymethylmethacrylate (PMMA) in FE during vertebroplasty in sheep.Methods In 8 sheep, two vertebral bodies were augmented alternatively with PMMA or bone wax. Pulmonary and cardiov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…pulmonary bone marrow fat embolization, was characterized by a sudden (within 60 s after injection) and considerable ([50%) increase in pulmonary arterial pressure which is in accordance with previous investigations [13,17]. Pulmonary hypertension lasted for 9 min.…”
Section: Effect Of Lavagesupporting
confidence: 90%
See 2 more Smart Citations
“…pulmonary bone marrow fat embolization, was characterized by a sudden (within 60 s after injection) and considerable ([50%) increase in pulmonary arterial pressure which is in accordance with previous investigations [13,17]. Pulmonary hypertension lasted for 9 min.…”
Section: Effect Of Lavagesupporting
confidence: 90%
“…There were significantly (P = 0.022) more fat droplets present in the control lung tissue requires an animal model suited to inject a similar quantity of bone cement and thus forcing a similar quantity of bone marrow into the circulation as in the clinical situation. Previous studies have shown that the sheep model is suitable to elicit reproducible and well-defined fat embolism and subsequent cardiovascular changes [13,14,20]. The sheep was therefore chosen to investigate cardiovascular changes during percutaneous vertebroplasty, even though the sheep's vertebral bodies have a higher bone mineral density and therefore a lower quantity of bone marrow fat content compared to-especially osteoporotic-human patients (Benneker, Gisep, Krebs et al Percutaneous vertebroplasty in sheep; development of an animal model.…”
Section: Animal Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Cement was injected into three lumbar vertebrae (L2-L4) after a twenty-minute time-interval between injections. The duration of the time-intervals was sufficient for stabilization of cardiovascular parameters to a new steady state 10,11 . Postinjection evaluation of cardiac output and blood gas parameters was carried out one minute and ten minutes after having started the first injection; ten minutes after having started the second injection; and ten minutes, thirty minutes, and sixty minutes after having started the third injection.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Aebli et al 10 demonstrated the embolization of bone marrow fat during vertebroplasty in an animal model, using transesophageal echocardiography and histopathology of the lungs. Associated cardiovascular deterioration was characterized by transient but severe pulmonary hypertension, arterial hypotension, decreased cardiac output, and respiratory acidosis in this animal model 11 . Fat embolism is a well-known complication during total hip and knee arthroplasty [12][13][14][15] , intramedullary reaming 16,17 , and Disclosure: In support of their research for or preparation of this work, one or more of the authors received, in any one year, outside funding or grants in excess of $10,000 from the Wesley Foundation, Brisbane, Australia; the AO Foundation, Davos, Switzerland; and AOSpine, Dübendorf, Switzerland (SRN 02/105).…”
mentioning
confidence: 99%